Answer:
x=0 y=-11 (0,-11)
Step-by-step explanation:
1. take what y equals (3x-11) and plug it in for y in the second equation
Should look like this: O= 6x-2(3x-11)-22
2. Then distribute O=6x-6x+22-22
3. Then combine like terms O= 0 the 22's cancel out as well as the x's
x= 0
4. plug 0 in for x in the first equation y=3(0)-11
5. y= -11
6. x=0 y=-11 (0,-11)
Answer:
c
Step-by-step explanation:
she pays a one-time fee of 50, and 15$ per month
So 3 and 1/4 is equal to 4/4+4/4+4/4+1/4=13/4
so she put in 3 and 1/9 or 9/9+9/9+9/9+1/9 or 28/9
28/9+x=13/4
13/4-28/9=x
so we convert so that the bottom numbers are the same
a short cut is 3 and 1/4+x=3 and 1/9
3 1/9+x=3 1/4
subtract 3 from both sides
1/9+x=1/4
subtract 1/4 from both sides
x=1/4-1/9
convert bottom number to same thing
1/9=4/36
1/4=9/36
x=9/36-4/36
x=5/36
5/36 cups
Answer:
x=-5 & y=-2
Step-by-step explanation:
y= 3x+13
y= x-3
x-3=3x+13
-3=2x+13
-10=2x
x=-5
then
y=3(-5)+13
y=-15+13
y=-2